2007
DOI: 10.1016/j.jconrel.2007.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular drug release kinetics dictate arterial drug deposition, retention, and distribution

Abstract: Millions of patients worldwide have received drug-eluting stents to reduce their risk for in-stent restenosis. The efficacy and toxicity of these local therapeutics depend upon arterial drug deposition, distribution, and retention. To examine how administered dose and drug release kinetics control arterial drug uptake, a model was created using principles of computational fluid dynamics and transient drug diffusion-convection. The modeling predictions for drug elution were validated using empiric data from ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 32 publications
2
115
0
Order By: Relevance
“…In fact, diffusion kinetics modeling of stent struts points toward serum diffusion as an important mechanism of drug delivery into the local endothelium. 37,38 In addition, oral administration of cell-cycle inhibitors prevent in-stent restenosis as well atherosclerotic progression in heart transplant patients, suggesting that serological delivery of drug, without high tunical concentrations, is able to affect stenotic progression. 9,29 Downstream endothelial effects should therefore be expected, in addition to effects on circulating macrophages and lymphocytes that are central to the development and progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, diffusion kinetics modeling of stent struts points toward serum diffusion as an important mechanism of drug delivery into the local endothelium. 37,38 In addition, oral administration of cell-cycle inhibitors prevent in-stent restenosis as well atherosclerotic progression in heart transplant patients, suggesting that serological delivery of drug, without high tunical concentrations, is able to affect stenotic progression. 9,29 Downstream endothelial effects should therefore be expected, in addition to effects on circulating macrophages and lymphocytes that are central to the development and progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…While it is evident that a DES manages to suppress neointimal growth, it can also provoke inflammatory response and local toxicity by interfering with cellular activities. All drugs work in limited therapeutic windows where an increase/decrease or major variation in the amount of drug exposed to the procedural segment can lead to serious conditions like thrombosis and inadequate healing; hence, arterial drug dose and release kinetics are critical parameters that should be studied thoroughly to ensure device safety and efficacy (Balakrishnan et al, 2007;Prabhu and Hossainy, 2006). The key to ideal procedural success requires optimization of drug dose and modulation of release kinetics which inhibit excess smooth muscle cell growth and does not affect the normal arterial endothelization process.…”
Section: Importance Of Controlled Drug Elution For Desmentioning
confidence: 99%
“…The respective models developed thereafter (Heller and Baker, 1980;Lee, 1980) prior the advent of DES are based on different controlled drug delivery systems but provided basic fundamentals that suggested appropriate mathematical simulations for drug delivery via DES. Recently, Balakrishnan et al (2007) demonstrated tissue drug uptake resulting from a range of administered drug dose and release kinetics using a 2-dimensional transient diffusionconvection computational model. They found that a simple Fickian diffusion model of drug transport in the coating can approximate the process in which the drug navigates through a complex porous polymeric coating.…”
Section: Computational Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Often with biological modelling it is necessary to make assumptions when applying boundary conditions. For example treating the artery wall as rigid (Mongrain et al, 2007;Devereux, 2005;Kaazempur-Mofrad and Ethier, 2001) or assuming that mass transport within the wall is modulated solely by diffusion (Balakrishnan et al, 2008(Balakrishnan et al, , 2007(Balakrishnan et al, , 2005Mongrain et al, 2007Mongrain et al, , 2005 are two examples of ways commonly employed to simplify what is in reality a very complex problem. However, as previously mentioned the fundamental in vivo issues should be taken into account as much as possible when applying such simplifications.…”
Section: Typical Computational Boundary Conditions For Des Modelsmentioning
confidence: 99%